A novel FPGA-based wireless vision sensor node - Chao Hu Zhiyong; Liu Yingzi Pan; Zhenxing Zeng; Meng, M.Q.-H. (2009 IEEE International Conference on Automation and Logistics, 2009)
Recent advances in wireless communication, semiconductor, embedded system and sensor technology have made it possible to build low cost, low power consumption, reconfigurable wireless vision sensor nodes. Wireless vision sensor networks, which consist of wirelessly connected embedded systems with vision capabilities, provide wide a variety of applications that are impossible to be realized with the vision systems with wired connection or the scalar-data based wireless sensor networks. In this paper, a novel wireless vision sensor node with the FPGA+microcontroller system on programmable chip (SOPC) architecture is presented. Especially, image compression problem of the wireless vision sensor node is discussed in detail. The experimental results show that the proposed technique is feasible.